2023
DOI: 10.5620/eaht.2023023
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution, placental transfer and excretion of silver nanoparticles in pregnant rats after a single oral dose

Khaled Y. Abdel-Halim,
Elsayed I. Salim,
Ahmed S. Abdel-Latif
et al.

Abstract: A quantitative assessment of silver nanoparticles (AgNPs) in fluids and some organs of pregnant rats as well as their fetal blood were carried out in this study. A single oral dose (1mg/kg) of AgNPs with a size range of 4-20 nm was administered to pregnant rats on the 19th of gestation. Five groups were euthanized after 10 min, 1, 6, 12, and 24 hr as well as the control group. Total Silver (Ag) contents were measured in bloods (maternal and fetal) and several organs using Inductive Coupled Plasma Optical Emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…113 Similarly, silver nanoparticles (AgNPs) with a size range of 4−20 nm were rapidly absorbed in the gastrointestinal tract following their oral administration to pregnant rats. 114 The cumulative excretion values of AgNPs showed a renal excretion level of 8.25%, which was higher than the fecal excretion level of 4.77% after 24 h. 114 The results showed that AgNPs accumulated within the body of pregnant rats and also transferred to the fetus which may lead to adverse effects. 114 Despite numerous studies that have been conducted to investigate and predict the effects of nanoparticles on pregnant subjects, there appears to be no NP-PBPK model that has been developed for such specific cases.…”
Section: Casesmentioning
confidence: 98%
See 2 more Smart Citations
“…113 Similarly, silver nanoparticles (AgNPs) with a size range of 4−20 nm were rapidly absorbed in the gastrointestinal tract following their oral administration to pregnant rats. 114 The cumulative excretion values of AgNPs showed a renal excretion level of 8.25%, which was higher than the fecal excretion level of 4.77% after 24 h. 114 The results showed that AgNPs accumulated within the body of pregnant rats and also transferred to the fetus which may lead to adverse effects. 114 Despite numerous studies that have been conducted to investigate and predict the effects of nanoparticles on pregnant subjects, there appears to be no NP-PBPK model that has been developed for such specific cases.…”
Section: Casesmentioning
confidence: 98%
“…Similarly, silver nanoparticles (AgNPs) with a size range of 4–20 nm were rapidly absorbed in the gastrointestinal tract following their oral administration to pregnant rats . The cumulative excretion values of AgNPs showed a renal excretion level of 8.25%, which was higher than the fecal excretion level of 4.77% after 24 h . The results showed that AgNPs accumulated within the body of pregnant rats and also transferred to the fetus which may lead to adverse effects .…”
Section: Pharmacokinetic Studies For Specialized Casesmentioning
confidence: 99%
See 1 more Smart Citation